2005
DOI: 10.1021/ie050260v
|View full text |Cite
|
Sign up to set email alerts
|

Radial-Flow Reactor Packed with a Catalytic Cloth:  Nitrate Reduction in Hydrogen-Saturated Water

Abstract: A novel flow reactor packed with a fibrous catalytic cloth is proposed to carry out a gas-liquid reaction. Radial flow and separation of the transport of the gaseous reactant and the reaction are the main features of the new design. An activated carbon cloth supported 2 wt % Pd-0.6 wt % Cu bimetallic catalyst installed in the reactor was applied for the water-phase nitrate hydrogenation, showing selectivity up to 84% toward nitrogen at a nitrate conversion of up to 93%. The reactor performance has been evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Moreover, alloying of metals may result in important changes in their activity and selectivity . The selection of the support is also important for this process, since it was shown that the support affects the catalyst activity and selectivity. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alloying of metals may result in important changes in their activity and selectivity . The selection of the support is also important for this process, since it was shown that the support affects the catalyst activity and selectivity. , …”
Section: Introductionmentioning
confidence: 99%
“…However, nitrate in the groundwater of some regions is as high as 50 mgN/L. Biological and physicochemical treatment has been developed to deal with excess nitrate, but catalytic denitridation as an emerging technology has attracted intensive attention because of its more economical and ecological merits .…”
Section: Introductionmentioning
confidence: 99%
“…Biological and physicochemical treatment has been developed to deal with excess nitrate, but catalytic denitridation as an emerging technology has attracted intensive attention because of its more economical and ecological merits. [1][2][3] Since 1989, when a Pd-Cu bimetal catalyst was found to be active by Tacke and Vorlop, 4,5 the activity and selectivity of nitrate hydrogenation on Pd-Cu bimetallic catalysts have been extensively discussed and found to be related to the structure of active components and the properties of supports. Various supports such as Al 2 O 3 , 6,7,11,14,17 clay, 9 active carbon, 18,19,22,23,26 beta-zeolite, 20,21 ZrO 2 , 10 SnO 2 , 15 Pumice, 11 glass fiber, 12 resins, 13,25 hydrotalcite, 8,16 TiO 2 , 27 and mordenite 24 have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Other important aspects fundamental to NO 3 RR, such as the reactor design, membrane development, optimal operating conditions, etc. , are beyond the scope of this review and can be found elsewhere. Finally, the challenges and future perspectives in this field are provided, aiming to stimulate more insights and invoke new design strategies for future catalyst development.…”
Section: Introductionmentioning
confidence: 99%